The Effect of a Cooperative Inquiry-Based Learning Program on Developing Preparatory School Students’ EFL Reading comprehension and Self-Regulation - Ahmed Ibrahim, Aya Mohamed; Hamdy, Azza Ahmed; Kamel Hassan, Magda (Journal of Neonatal Surgery, 2025)
The current study aimed at investigating the effect of a cooperative inquiry-based learning program on developing preparatory school students’ EFL reading comprehension and self-regulation. The study adopted the quasi-experimental design. The participations were forty students from preparatory stage enrolled in the second grade from Bahtit, Abo Hamad Directorate, Sharkia Governorate, who were equally divided into two groups: experimental group and control group. The experimental group was taught by the cooperative inquiry-based learning program while the control group received regular instruction in the first semester of the academic year (2025-2026). The experiment lasted for eight weeks. The researcher carried out ten sessions; each session took about 120minutes. So, the treatment took about 20hours. To achieve the aim of the study, the researcher designed these instruments, an EFL reading comprehension skills checklist, a pre-post reading comprehension skills test, a rubric of the reading comprehension skills test, and a pre-post self-regulation scale. The data obtained were statistically treated through the SPSS program. Results showed that the experimental group outperformed the control group in both reading comprehension skills and self-regulation due to the use of the cooperative inquiry-based learning program. These results indicated that cooperative inquiry-based learning program has a large effect on developing preparatory school students' EFL reading comprehension, and self-regulation.